Nasal and sinonasal tumors formed by atypical adenomatous lesions arising in respiratory epithelial adenomatoid hamartoma/seromucinous hamartoma - Michal, Michal; Skálová, Alena; Hyrcza, Martin; Laco, Jan; Vaněček, Tomáš; Rupp, Niels J.; Michal, Michael; Michalová, Květoslava; Agaimy, Abbas; Bradová, Martina (Virchows Archiv, 2023)
Two benign adenomatous lesions are commonly recognized within the sinonasal tract, namely respiratory epithelial adenomatoid hamartoma (REAH) and seromucinous hamartoma (SH). We present 10 hitherto unrecognized benign polypoid nasal and sinonasal tumoriform lesions having in average 3.6 cm in largest dimension, which are histogenetically related to SH and REAH. In addition to typical structures of REAH and SH, these lesions contained an additional characteristic and slightly atypical adenomatous component, which we termed atypical sinonasal glands arising in SH (ASGSH). ASGSH often produced deep red colored secretion with peripheral clearing similar to that seen in thyroid follicles. In contrast to SH, ASGSH was endowed by both secretory and myoepithelial layers and had mostly angulated shapes with snout-like protrusions into the lumens. Both layers were formed by an irregular, disorganized, and often incomplete cell lining, which had slightly atypical cytological features without mitoses. In 3 cases, ASGSHs revealed sebaceous differentiation, and in 3 cases the stroma produced a well-differentiated cartilage. Neoplastic nature of ASGSH was supported by finding of various mutations as revealed by next generation sequencing in five cases. In two cases each, we found identical mutations in BRAF gene (Val600Glu), and RET gene (Arg912Trp), respectively and in one case FAT1 gene alteration (Pro1665Leu).
CRIS-Team Scopus Importer:2023-12-22
Keywords: Atypical adenomatous lesions arising in REAH/seromucinous hamartoma; REAH; Respiratory adenomatoid hamartoma; Sebaceous differentiation; Seromucinous hamartoma